2011
DOI: 10.1021/ma201169z
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy for Control of “Random” Copolymerization of Lactide and Glycolide: Application to Synthesis of PEG-b-PLGA Block Polymers Having Narrow Dispersity

Abstract: Poly(lactic-co-glycolic acid) (PLGA) is a biodegradable copolymer that is also acceptable for use in a variety of biomedical applications. Typically, a random PLGA polymer is synthesized in a bulk batch polymerization using a tin-based catalyst at high temperatures. This methodology results in relatively broad polydispersity indexes (PDIs) due to transesterification, and the polymer product is often discolored. We report here the use of 1,8-diazabicyclo[5.4.0]-undec-7-ene (DBU), a known, effective, and conveni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
133
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(142 citation statements)
references
References 42 publications
(106 reference statements)
4
133
0
1
Order By: Relevance
“…In preclinical experiments, the PLA was shown to be biodegraded through hydrolysis after intravenous administration within few days, (7) while low molecular weight PEG (M w <10 kDa) is thought to be eliminated by renal clearance (8). From an industrial standpoint, the synthesis of the copolymer by ring-opening polymerization is well-documented and can be performed at multi-gram scale with satisfying purity (9). Finally, the accumulated knowledge of the biopharmacy and the physico-chemistry of these nanoassembled copolymers is another advantage of PLA-PEG nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…In preclinical experiments, the PLA was shown to be biodegraded through hydrolysis after intravenous administration within few days, (7) while low molecular weight PEG (M w <10 kDa) is thought to be eliminated by renal clearance (8). From an industrial standpoint, the synthesis of the copolymer by ring-opening polymerization is well-documented and can be performed at multi-gram scale with satisfying purity (9). Finally, the accumulated knowledge of the biopharmacy and the physico-chemistry of these nanoassembled copolymers is another advantage of PLA-PEG nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…This result is not surprising as DBU and mPEG concentrations do not change during polymerization. Qian et al 34 have reported similar first-order dependency with respect to monomer, DBU, and macroinitiator concentrations for ROP of LA and glycolide. 34 Furthermore, ROP of valerolactone using similar amidine catalysts have been shown to follow firstorder kinetics with respect to catalyst, alcohol, initiator and monomer concentration.…”
Section: Discussionmentioning
confidence: 76%
“…Qian et al 34 have reported similar first-order dependency with respect to monomer, DBU, and macroinitiator concentrations for ROP of LA and glycolide. 34 Furthermore, ROP of valerolactone using similar amidine catalysts have been shown to follow firstorder kinetics with respect to catalyst, alcohol, initiator and monomer concentration. 35 Although we did not systematically study the polymerization kinetics upon addition of CB and LA, a time of 3 h was sufficient to obtain polymers with targeted mass ratios of MAC, CB, and LA for both mPEG 114 -b-PMAC 2.5 -b-P(CB 9 -co-LA 39 ) and mPEG 114 -b-P(CB 8 -co-LA 35 -co-MAC 2.5 ) copolymers (inferred from 1 H NMR spectra).…”
Section: Discussionmentioning
confidence: 76%
“…In the case of biomaterials, both biocompatibility and biodegradability are highly desirable properties. Aliphatic polyesters such as poly(lactic acid)s, poly(glycolic acid)s, and poly(amino acid)s have these properties [3][4][5]. Therefore, these modified copolymers are widely investigated for biomaterial applications.…”
Section: Introductionmentioning
confidence: 99%